Female genital schistosomiasis is a neglected public health problem in Tanzania: Evidence from a scoping review. - Gladys Mbwanji; Humphrey D Mazigo; Jane K Maganga; Jennifer A Downs (PLoS Neglected Tropical Diseases)
Schistosoma haematobium, the parasite that causes urogenital schistosomiasis, is widely prevalent in Tanzania. In addition to well-known effects on the urinary tract, S. haematobium also causes clinically- evident damage to the reproductive tract in approximately half of infected women, which is known as female genital schistosomiasis (FGS). FGS has major gynecologic and social consequences on women's reproductive health, yet little information is available regarding FGS in Tanzania. To cover that gap, we conducted the present scoping review to examine the epidemiology of FGS in Tanzania (both in the mainland and Zanzibar island) and to make recommendations for future work in this area. The available evidence from community-based and hospital-based retrospective studies indicates that FGS is a significant health problem in the country. Very few community-based studies have been reported from mainland Tanzania, and Zanzibar. Our review highlights the scarcity of efforts to address FGS in Tanzania and the need for additional community-based studies. The studies will help us understand the true burden of the disease nationwide, to assess the impact of praziquantel on FGS lesions, and to address social and mental health in relation to FGS. This review emphasizes integration of delivery of FGS related services in primary health care systems through the reproductive health clinics which covers sexually transmitted infections, HIV and cervical cancer screening. These actions are essential if this neglected gynecological disease is to be addressed in Tanzania.